Hematopoietic stem cell transplantation using single UM171-expanded cord blood: a single-arm, phase 1–2 safety and feasibility study. Issue 2 (February 2020) - Cohen, Sandra; Roy, Jean; Lachance, Silvy; Delisle, Jean-Sébastien; Marinier, Anne; Busque, Lambert; Roy, Denis-Claude; Barabé, Frédéric; Ahmad, Imran; Bambace, Nadia; Bernard, Léa; Kiss, Thomas; et al.
Summary: Background: Benefits of cord blood transplantation include low rates of relapse and chronic graft-versus-host disease (GVHD). However, the use of cord blood is rapidly declining because of the high incidence of infections, severe acute GVHD, and transplant-related mortality. UM171, a haematopoietic stem cell self-renewal agonist, has been shown to expand cord blood stem cells and enhance multilineage blood cell reconstitution in mice. We aimed to investigate the safety and feasibility of single UM171-expanded cord blood transplantation in patients with haematological malignancies who do not have a suitable HLA-matched donor. Methods: This single-arm, open-label, phase 1–2 safety and feasibility study was done at two hospitals in Canada. The study had two parts. In part 1, patients received two cord blood units (one expanded with UM171 and one unmanipulated cord blood) until UM171-expanded cord blood demonstrated engraftment. Once engraftment was documented we initiated part 2, reported here, in which patients received a single UM171-expanded cord blood unit with a dose de-escalation design to determine the minimal cord blood unit cell dose that achieved prompt engraftment. Eligible patients were aged 3–64 years, weighed 12 kg or more, had a haematological malignancy with an indication for allogeneic hematopoietic stem cell transplant and did not have a suitable HLA-matched donor, and a had a Karnofsky performance status score of 70% or more. Five clinical sites were planned to participate in the study; however, only two study sites opened, both of which only treated adult patients, thus no paediatric patients (aged <18 years) were recruited. Patients aged younger than 50 years without comorbidities received a myeloablative conditioning regimen (cyclophosphamide 120 mg/kg, fludarabine 75 mg/m 2, and 12 Gy total body irradiation) and patients aged older than 50 years and those with comorbidities received a less myeloablative conditioning regimen (cyclophosphamide 50 mg/kg, thiotepa 10 mg/kg, fludarabine 150 mg/m 2, and 4 Gy total body irradiation). Patients were infused with the 7-day UM171-expanded CD34-positive cells and the lymphocyte-containing CD34-negative fraction. The primary endpoints were feasibility of UM171 expansion, safety of the transplant, kinetics of hematopoietic reconstitution (time to neutrophil and platelet engraftment) of UM171-expanded cord blood, and minimal pre-expansion cord blood unit cell dose that achieved prompt engraftment. We analysed feasibility in all enrolled patients and all other primary outcomes were analysed per protocol, in all patients who received single UM171-expanded cord blood transplantation. This trial has been completed and was registered with ClinicalTrials.gov, NCT02668315 . Findings: Between Feb 17, 2016, and Nov 11, 2018, we enrolled 27 patients, four of whom received two cord blood units for safety purposes in part 1 of the study. 23 patients were subsequently enrolled in part 2 to receive a single UM171-expanded cord blood transplant and 22 patients received a single UM171-expanded cord blood transplantation. At data cutoff (Dec 31, 2018), median follow-up was 18 months (IQR 12–22). The minimal cord blood unit cell dose at thaw that achieved prompt engraftment as a single cord transplant after UM171 expansion was 0·52 × 10 5 CD34-positive cells. We successfully expanded 26 (96%) of 27 cord blood units with UM171. Among the 22 patients who received single UM171-expanded cord blood transplantation, median time to engraftment of 100 neutrophils per μL was 9·5 days (IQR 8–12), median time to engraftment of 500 neutrophils per μL was 18 days (12·5–20·0), and no graft failure occurred. Median time to platelet recovery was 42 days (IQR 35–47). The most common non-haematological adverse events were grade 3 febrile neutropenia (16 [73%] of 22 patients) and bacteraemia (nine [41%]). No unexpected adverse events were observed. One (5%) of 22 patients died due to treatment-related diffuse alveolar haemorrhage. Interpretation: Our preliminary findings suggest that UM171 cord blood stem cell expansion is feasible, safe, and allows for the use of small single cords without compromising engraftment. UM171-expanded cord blood might have the potential to overcome the disadvantages of other cord blood transplants while maintaining the benefits of low risk of chronic GVHD and relapse, and warrants further investigation in randomised trials. Funding: Canadian Institutes of Health Research, Canadian Cancer Society and Stem Cell Network.